2016
DOI: 10.2217/nnm-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flexing and Massage on in Vivo Human Skin Penetration and Toxicity of Zinc Oxide Nanoparticles

Abstract: Exposure of normal in vivo human skin to these nanoparticles under common in-use conditions of flexing or massage is not associated with significant adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 44 publications
8
47
0
1
Order By: Relevance
“…Gratieri et al [36] also showed that nanomaterials (diameter 4 nm) deposited on the skin furrows and follicles of intact human skin based on MPT and confocal laser scanning microscopy. This also concurs with our previous work on ZnO nanoparticles that showed no penetration into human skin in vivo when applied as sunscreen formulations [6], with occlusion [8], with massage and flexing [7], and with repeated application [9]. However, these nanoparticles were larger (65–75 nm) and had the potential to agglomerate in the formulation.…”
Section: Discussion/conclusionsupporting
confidence: 91%
See 1 more Smart Citation
“…Gratieri et al [36] also showed that nanomaterials (diameter 4 nm) deposited on the skin furrows and follicles of intact human skin based on MPT and confocal laser scanning microscopy. This also concurs with our previous work on ZnO nanoparticles that showed no penetration into human skin in vivo when applied as sunscreen formulations [6], with occlusion [8], with massage and flexing [7], and with repeated application [9]. However, these nanoparticles were larger (65–75 nm) and had the potential to agglomerate in the formulation.…”
Section: Discussion/conclusionsupporting
confidence: 91%
“…The majority of well-conducted studies of ZnO nanoparticles have concluded that these nanoparticles do not penetrate healthy adult human skin [6-8]. ZnO nanoparticles (average size 80 nm) were not transported into viable epidermis even with mechanical stress such as flexing and massage [7], occlusion and barrier impairment [8] and repeated application [9]. Whilst this establishes the safety of these nanoparticle-based sunscreens, it must be noted that the nature of the formulation may influence the tendency of these nanoparticles to remain on the skin surface and furrows.…”
Section: Introductionmentioning
confidence: 99%
“…Because, nanomaterials have smaller sizes and corresponding larger specific surface area than micromaterials (Kipen and Laskin 2005, Oberdorster et al 2005, Nel et al 2006. Many researchers and we have studied the different potential effects of nanomaterials with various compositions and properties on human and environmental health in vitro and in vivo settings (Sonmez et al 2015, Leite-Silva et al 2016, Turkez et al 2016. Nanostructures of silicon, including particles, dots, wires, rods and ribbons, have sparked much interest due to their unique electronic/mechanical properties and the improved performances, and make their potential application in many areas such as optoelectronic devices, solar cells and biological markers (Chantrenne and Lysenko 2005, Cavarroc et al 2006, Zschech et al 2007, Baca et al 2007, Schmidt et al 2009, Heintz et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…We followed this approach by developing SLNs loaded with vegetable oils from Brazilian flora, which is rich in antioxidant substances. We used a powerful multiphoton imaging technique (MPT-FLIM) to verify interaction between formulations and skin in human volunteers, as well as ex vivo (Franz cell) tests of skin permeation [18,19,24,25,26]. …”
Section: Resultsmentioning
confidence: 99%
“…FLIM images were taken at 3 depths within the viable epidermis corresponding to the stratum granulosum, stratum spinosum, and stratum basale. FLIM images were analyzed with SPC Image 5.2 software (Becker & Hickl, Berlin, Germany) as previously described [18,19]. …”
Section: Methodsmentioning
confidence: 99%